2013
DOI: 10.4103/2224-3151.115830
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of dengue in South-East Asia

Abstract: The burden of dengue and its potential threat to global health are now globally recognized, with 2.5 billion people at risk worldwide. The pathogenesis of severe dengue is particularly intriguing with the involvement of different immune factors. Also, the epidemiology of dengue in South-East Asia is undergoing a change in the human host, the dengue virus and the vector bionomics. Shift in affected age groups, sex differences and expansion to rural areas are evident, while the virulence and genotype of the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 20 publications
1
29
0
3
Order By: Relevance
“…In Southeast Asia, where dengue has been circulating for much longer, there is evidence of an increase in the incidence of dengue towards older age groups [90] and that this age shift has led to dengue primarily affecting the adult population in some countries [91]. A previous systematic review of the epidemiology and burden of dengue in Latin America and the Caribbean reported that adults aged 15 to 59 years were the age group most affected [92].…”
Section: Discussionmentioning
confidence: 99%
“…In Southeast Asia, where dengue has been circulating for much longer, there is evidence of an increase in the incidence of dengue towards older age groups [90] and that this age shift has led to dengue primarily affecting the adult population in some countries [91]. A previous systematic review of the epidemiology and burden of dengue in Latin America and the Caribbean reported that adults aged 15 to 59 years were the age group most affected [92].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclical outbreaks of dengue of increasing magnitude have been observed with a cycle of 5–6 years ( 4 ), but this pattern appeared to cease in 2005, and no obvious cycle has occurred since then. Although other tropical and subtropical countries in Southeast Asia have distinct seasonality ( 5 ) so that dengue epidemics occur at distinct and predictable times of the year ( 6 ), Singapore’s proximity to the equator gives it an aseasonal climate, and the timing of dengue epidemics is irregular ( 7 , 8 ). …”
mentioning
confidence: 99%
“…The movement of equipment and other war activities resulted in the transport of mosquitoes and their eggs to new geographic areas (Guzman et al, 2010). The result was a greatly expanded geographic distribution and increased densities of A. aegypti and increased epidemic dengue activity (Bhatia et al, 2013). The economic expansion was the driving force of unprecedented urban growth that continues today (Ferreira, 2012).…”
Section: Factors Responsible For the Global Resurgence Of Denguementioning
confidence: 99%
“…During the 1960s and 1970s the disease caused outbreaks in India, Malaysia, Singapore, Vietnam, Indonesia, and Myanmar. From the 1970s to the present time, there has been a dramatic geographic expansion of epidemic DHF in the countries of Asia and from there to the Pacific and the Americas (Bhatia et al, 2013). Japan routinely experienced dengue epidemics in its southern islands of Okinawa and Formosa (Taiwan), but the Japanese mainland was not affected until the Second World War (Hotta, 1953).…”
Section: Factors Responsible For the Global Resurgence Of Denguementioning
confidence: 99%